2022
DOI: 10.1126/scitranslmed.abj1270
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cancer glycosylation repolarizes tumor-associated macrophages allowing effective immune checkpoint blockade

Abstract: Immune checkpoint blockade (ICB) has substantially improved the prognosis of patients with cancer, but the majority experiences limited benefit, supporting the need for new therapeutic approaches. Up-regulation of sialic acid–containing glycans, termed hypersialylation, is a common feature of cancer-associated glycosylation, driving disease progression and immune escape through the engagement of Siglec receptors on tumor-infiltrating immune cells. Here, we show that tumor sialylation correlates with distinct i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 55 publications
2
66
0
Order By: Relevance
“…As a result, mice transplanted with Fut8 KO hematopoietic bone marrow displayed enhanced resistance to inflammation [ 71 ]. In addition, macrophages represent one the largest leukocyte population in various tumor microenvironments and have been described to display unusual glycosylation patterns, which have, in turn, been proposed as potential therapeutic targets [ 72 , 73 , 74 , 75 ].…”
Section: Fucosylation Interplay With the Immune System And Hormonal P...mentioning
confidence: 99%
“…As a result, mice transplanted with Fut8 KO hematopoietic bone marrow displayed enhanced resistance to inflammation [ 71 ]. In addition, macrophages represent one the largest leukocyte population in various tumor microenvironments and have been described to display unusual glycosylation patterns, which have, in turn, been proposed as potential therapeutic targets [ 72 , 73 , 74 , 75 ].…”
Section: Fucosylation Interplay With the Immune System And Hormonal P...mentioning
confidence: 99%
“…[67] Recently, therapeutic desialylation using an antibody-sialidase conjugate represents an immunotherapeutic approach to reshape macrophage phenotypes and augment the adaptive antitumor immune response. [68] By combining both tools of sialidase and sialylation inhibitor, O'Dwyer et al observed a better efficacy of NK cells against multiple myeloma. [26] Besides that, sLe X epitopes modulate the leukocyte homing, and some GBPs, such as Siglec-7/15 [69] and galectin-1/3, [70] are newly identified as immune checkpoints and have driven immense attention to improving ACT therapeutic efficacy.…”
Section: Adoptive Cancer Immunotherapymentioning
confidence: 99%
“…Recombinant sialidase and trastuzumab conjugates were developed to selectively desialylate the human epidermal growth factor receptor 2 (HER2)‐positive tumor cells, which increased the susceptibility of cancer cells and ADCC [67] . Recently, therapeutic desialylation using an antibody‐sialidase conjugate represents an immunotherapeutic approach to reshape macrophage phenotypes and augment the adaptive antitumor immune response [68] . By combining both tools of sialidase and sialylation inhibitor, O′Dwyer et al.…”
Section: Therapeutic Opportunities Driven By Live‐cell Glycocalyx Eng...mentioning
confidence: 99%
“…The application of AAC chemistry in polysaccharides has contributed to generate complex glycoconjugates that allowed the development of new biomaterials exhibiting improved properties and functions (Elchinger et al, 2011), assuring high yields and highly selective products by carbon-hetero bond formation reactions, which results in the formation of a triazole ring unit (Tan et al, 2018). On the other hand, it is (Cioce et al, 2022;Stanczak et al, 2022).…”
Section: Click Chemistrymentioning
confidence: 99%
“…In this scope, we highlight the recent Nobel Prize in Chemistry in which Carolyn Bertozzi has applied such elegant and efficient chemical reaction inside living organisms, without disrupting the normal cell chemistry. Such development has leveraged click chemistry to a new dimension, affording to map cells and track biological processes as well as to improve the targeting of cancer pharmaceuticals ( Cioce et al, 2022 ; Stanczak et al, 2022 ).…”
Section: Chemical and Structural Modification Of Marine Polysaccharidesmentioning
confidence: 99%